الأحكام التي يشترك فيها التكسير والتصغير - السلمي, رفيع بن فازي (Revues faculté des lettres et des langues; Vol. 1 No 21 (2017): مجلة كلية الآداب و اللغات, 2018)
Abstract: It is worth mentioning that grammarians have attempted to show the close relationship between the related chapters for the purpose of learning about the general principles. In fact they have set common rules with respect to the broken plural and the diminutive pattern. They sometimes set the broken plural before the diminutive pattern and vice versa though they insist that both patterns are of the same category. I have traced and meditated this category until I have found a research appropriate material that , to the best of my knowledge , has not been addressed by researchers yet. Afterwards ,I have applied myself to determine the purpose of those researchers beyond their above category , and the common rules between both patterns attempting to identify the statements of grammarians whether they have set the broken plural before the diminutive pattern or the opposite, as well as careful study of such rules that exhibit the agreed and disagreed aspects , and what excluded or not ,recorded or not in both patterns or either of them , and to see which pattern is set before the other along with the most accurate statements of the grammarians as to the description of the rules. الملخص مما يلفت النظر في مجال جهود علماء النحو في استظهار صلات الرحم بين الأبواب بغية الإحاطة بالأصول العامة أنهم ينصون على أحكام مشتركة بين بابي التكسير والتصغير ، ويصرحون تارة بحمل التكسير على التصغير ، وتارة أخرى بحمل التصغير على التكسير، ويكررون مقولة " التصغير والتكسير من وادٍ واحد "، فأخذت أتتبع وأتأمّل فعلهم هذا إلى أن تحصلّت على مادة صالحة للبحث لم يقف عليها أحد من الباحثين حسب اطلاعي. بعد ذلك عكفت على تحديد المراد من مقولتهم السابقة، وجمع الأحكام المشتركة بين البابين، ومعرفة أقوال النحويين في حمل التصغير على التكسير أو العكس ، ودراسة تلك الأحكام دراسة تامة تكشف : ما اُتّفق عليه منها، وما لم يُتّفق ، وما اُطّراد منها أو قُيِّد في البابين أو في أحدها وما لم يَطّرد أو يُقيّد، وأيَّ البابين أولى بالحمل على الآخر، وأدقَّ عبارات النحويين في توصيف الحكم .